PENGEMBANGAN E-GOVERNMENT DALAM PENYELENGGARAAN TATA KELOLA PEMERINTAHAN DAERAH DI PROVINSI RIAU TAHUN 2016 - Lydia Iswandi; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The reform era was marked by the demands of good governance that required transparency, effectiveness and efficiency, accountability and public participation in every process of public policy. Technological advances are very fast motivating the government to create a new revolution in the form of the shifting of manual work systems into digital by implementing E-Government as a form of governance governance reform to realize more affordable service practices and expand public access to information. Based on Presidential Instruction No. 03 of 2003 concerning National Policy and Strategy for E-Government development.Based on the background of the problem that the author mentioned above, then the related matter is the main problem in this study, namely: How is the development of E-Government in the implementation of Regional Governance in Riau Province in 2016 and what are the inhibiting factors for E-Government development in implementation of regional governance in Riau Province in 2016. In carrying out this research, the author uses a qualitative approach and descriptive type of research, which conducts research directly at the location or place studied aims to obtain a clear and complete description of a situation or problem under studyThe results of the study found that the development of E-Government in the Regional Government of Riau was already at the maturation stage with the implementation of each level of E-Government development strategy in accordance with Presidential Instruction No. 03 of 2003. While the obstacles encountered in E-Government development were internalized: maximum network security, less availability of general data, development data and spatial data, and budget constraints. External barriers: low public knowledge of information technology, lack of commitment of each Riau Province SKPD and District / City SKPD on data integrity, data exchange and data entry and high public information disputes.Keywords: Development, E-Government, Governance